Emergency liquidity facilities, signalling and funding Costs - Céline Gauthier; Alfred Lehar; Héctor Pérez Saiz; Moez Souissi (Bank of Canada, 2015)
In the months preceding the failure of Lehman Brothers in September 2008, banks were willing to pay a premium over the Federal Reserve's discount window (DW) rate to participate in the much less flexible Term Auction Facility (TAF). We empirically test the predictions of a new signalling model that offers a rationale for offering two different liquidity facilities. In our model, illiquid yet solvent banks need to pay a high cost to access the TAF as a way to signal their quality, in exchange for more favourable funding in the future. Less solvent banks access the less costly and more flexible DW in case they experience an unexpected run, paying a higher future funding cost. The existence of two facilities with different characteristics allowed banks to signal their level of solvency, which helped to decrease asymmetric information during the crisis. Using recently disclosed data on access to these facilities, we provide evidence consistent with these results. Banks that accessed TAF in 2008 paid approximately 31 basis points less in the interbank lending market in 2010 and were perceived as less risky than banks that accessed the DW. Our results can contribute to a better design of liquidity facilities during a financial crisis.
Keywords: G21; G28; G01; 330; Financial stability; Financial institutions; Lender of last resort